Comparative Proteomic Analysis of Soybean Leaves and Roots by iTRAQ Provides Insights into Response Mechanisms to Short-Term Salt Stress - Ji, Wei; Cong, Ru; Li, Sheng; Li, Rui; Qin, Zhiwei; Li, Yanjun; Zhou, Xiaolin; Chen, Sixue; Li, Jing (Frontiers in Plant Science, 2016)
Salinity severely threatens land use capability and crop yields worldwide. Understanding the mechanisms that protect soybean from salt stress will help in the development of salt-stress tolerant leguminous plants. Here we firstly analyzed the changes in malondialdehyde levels, the activities of superoxide dismutase and peroxidases, cholorophyll contents, and Na+/K+ ratios in leaves and roots from soybean seedlings treated with 200 mM NaCl for different time points, and suggested that 200 mM NaCl treated for 12 h was enough for exploring proteomic analysis to soybean seedlings. iTRAQ-based proteomic approach was used to investigate the proteomes of soybean leaves and roots under salt treatment. Data are available via ProteomeXchange with identifier PXD002851. In total, 278 and 440 proteins with significantly altered abundance were identified in leaves and roots of soybean, respectively, with only 50 mutual unique proteins in the both tissues. These identified differentially expressed proteins (DEPs) were mainly involved in 13 biological processes. Moreover, protein-protein interaction analysis revealed that the proteins involved in metabolism, carbohydrate and energy metabolism, protein synthesis and redox homeostasis constructed four types of response networks to high salt stress. Besides, semi-quantitative RT-PCR analysis revealed that some of the proteins, such as 14-3-3, MMK2, PP1, TRX-h, were also regulated by salt stress at the level of transcription. These results indicated that effective regulatory protein expression related to signalling, membrane and transport, stress defense and metabolism played important roles in the short-term salt response of soybean seedlings.